Oh, nuts! - Sauer, Tammi (Bloomsbury, 2012)
Chipmunks Cutesy, Blinky, and Bob want the same kind of attention people pay to other animals who live in the zoo, but when one of their plans succeeds, they see that being noticed is not always a good thing.